2015
DOI: 10.11604/pamj.2015.22.98.6399
|View full text |Cite
|
Sign up to set email alerts
|

Kaiy (traditional cautery) in Benghazi, Libya: complications versus effectiveness

Abstract: IntroductionThe practice of Kaiy (Cautery) as a traditional therapy is not science based though it is widely practiced worldwide. In Libya, in particular, it is commonly used with no any report or publication to emphasis on its positive or negative impact. This work was undertaken to highlight the complications and disadvantages of kaiy in the Libyan societies as it seems to cause more harm than benefit for the patient.MethodsWe conducted a questionnaire-based survey in the period from the first of March to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Respondents who were elderly and illiterate were also more exposed to traditional cautery, probably due to their poor knowledge, limited awareness on the harmful effects of cautery, and long-standing cultural beliefs. Similarly, other studies reported that traditional cautery was more common in the elderly and in the illiterate compared to their counterparts [6,12,13]. As most of the ethnic groups were Muslims, the higher practice compared to Tigrigna (mainly Christians) might be associated with high cultural and religious conviction and this was found to be consistent with a recently reported finding [2].…”
Section: Discussionsupporting
confidence: 88%
“…Respondents who were elderly and illiterate were also more exposed to traditional cautery, probably due to their poor knowledge, limited awareness on the harmful effects of cautery, and long-standing cultural beliefs. Similarly, other studies reported that traditional cautery was more common in the elderly and in the illiterate compared to their counterparts [6,12,13]. As most of the ethnic groups were Muslims, the higher practice compared to Tigrigna (mainly Christians) might be associated with high cultural and religious conviction and this was found to be consistent with a recently reported finding [2].…”
Section: Discussionsupporting
confidence: 88%
“…Cautery (kaiy in Arabic) is one of the oldest ancient healing techniques without any scientific evidence. Traditional healers performed cautery by burning specific skin points according to the treated disease [ 66 ]. Severe complications were reported after cauterization.…”
Section: The Most Used Tandcm Therapies In Saudi Arabiamentioning
confidence: 99%
“…Of these who practiced cautery, self-reported improvement was substantial, similar to reported in the Israeli study [ 8 ]. Moreover about one in ten patients encountered treatment complications in this study while, according to [ 12 ], 63.5% of participants did not improve after cauterization and developed adverse events and complications. The most common complications were body disfigurement and infection.…”
Section: Discussionmentioning
confidence: 78%
“…About three-fourth of the study participants disclosed that they did not inform healthcare professionals, about their history of traditional cautery, during their visit to health facilities. Majority of those who did cautery in past followed their relatives´ advice; whilst in a study conducted in Libya, it was reported as 90% [ 12 ]. Of these who practiced cautery, self-reported improvement was substantial, similar to reported in the Israeli study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%